An increase in plasma adiponectin multimeric complexes follows hypocaloric diet-induced weight loss in obese and overweight pre-menopausal women - Polak, Jan; Kovacova, Zuzana; Jacek, Martin; Klimcakova, Eva; Kovacikova, Michaela; Vitkova, Michaela; Kuda, Ondrej; Sebela, Marek; Samcova, Eva; Stich, Vladimir (Clinical science (London, England, 2007)
Adiponectin is involved in the regulation of glucose and fatty acid metabolism, influences whole-body insulin sensitivity and protects arterial walls against the development of atherosclerosis. Plasma adiponectin is decreased in obese, insulin-resistant and Type 2 diabetic patients. Adiponectin circulates in plasma as high-, medium- and low-molecular-weight ('mass') forms (HMW, MMW and LMW respectively). The HMW form is believed to be closely associated with insulin sensitivity. The aim of the present study was to investigate whether diet-induced changes in body weight and insulin sensitivity were associated with changes in the quantity of adiponectin multimeric complexes. A total of 20 overweight or obese women (age, 39.4+/-9.5 years; body mass index, 32.2+/-6.4 kg/m(2)) underwent 12 weeks of low caloric diet (600 kcal/day less than energy requirements; where 1 kcal is approximately 4.184 kJ). Plasma samples were drawn before and after the study for biochemical analysis and Western blot detection of adiponectin multimeric complexes. The hypocaloric diet resulted in a weight reduction (89.8+/-16.4 kg compared with 83.1+/-15.6 kg; P<0.001) and an improvement in whole-body insulin sensitivity, as measured by HOMA (homoeostasis model assessment index; 1.9+/-0.8 compared with 1.5+/-0.7; P=0.013). Increases in the quantities of the HMW, MMW and LMW forms by 5.5, 8.5 and 18.1% respectively, were observed (P<0.05 for all of the forms). Total plasma adiponectin was increased by 36% with borderline significance (P=0.08). No correlations between changes in adiponectin complexes and changes in indices of insulin sensitivity were observed. In conclusion, diet-induced weight loss improved insulin sensitivity as well as increased the amount of HMW, MMW and LMW adiponectin complexes in plasma.
Keywords: obezita; Premenopause; hmotnostní úbytek; Humans; redukční dieta; kalorická restrikce; Caloric Restriction; premenopauza; Overweight; Diet, Reducing; Female; dospělí; ELISA; lidé; Enzyme-Linked Immunosorbent Assay; Adult; ženské pohlaví; Adiponectin; Weight Loss; adiponektin; Obesity; nadváha